Wearing someone else's shoes. Issue 1 (21st June 2010) - Rae, Kym
Abstract : This paper recounts a journey of discovery by a scientist who inadvertently takes on coordination of an ArtsHealth programme. The dynamics of role change are explored showcasing the vulnerabilities and fears that often accompany these career adjustments. The associated ArtsHealth programme ( Gomeroi gaaynggal) works with Aboriginal and Torres Strait Islander women in Australia throughout their pregnancy to improve understanding of issues that impact the health of themselves and their developing baby. By wearing someone else shoes, the scientist is immersed in the project and must confront issues including skill mix, learning and cultural diversity.